Ictech wizard : foundation level (the city school) (Albakio/The city school Lahore, 2012)
An educational resource designed to introduce foundational concepts in information and communication technology (ICT) to young learners. The book includes interactive activities and clear explanations to help students develop essential ICT skills, preparing them for more advanced topics in the digital world.